FEMINISME DALAM FILM MONALISA SMILE - Sephira Ayu Irawan (Konvergensi, 2015)
Feminist studies in a film titled Mona Lisa Smile. Using semiotic analysis in its formulation. Feminist struggle seemed to have no end, although the portrait of women today have far different from the past. In the past, women are regarded as second-class citizens, stereotype that women are home space are largely determined on how female expression. Feminist grappling on the ideas of equality, classic feminist opinion of the 19th century to equate women with men should be through access to educational institutions, and the public sphere. In the film Mona Lisa Smile women found a lot of resistance, but the study also found a gag subtly of the types of resistance were carried out. Key Word : Feminism, Film, Resistance, Muted Group.